Comparison of the business sustainability perception of Malaysian manufacturing SMEs / Yusmazida Mohd Yusoff... [et al.] - Mohd Yusoff, Yusmazida; Omar, Muhamad Khalil; Ahmad Zayadah, Mazlina (Universiti Teknologi MARA Cawangan Selangor, 2020)
The objective of this study is to determine the comparison of business sustainability practices according to demographic profile of manufacturing SMEs. The model of the survey is a descriptive survey model. There are 22 items on business sustainability that formed a part of a questionnaire using a five-point interval scale. Data were gathered from 168 respondents who were chosen by purposive sampling. A survey form was used as the data-gathering tool in the study. The data analysis in the study was conducted by using SPSS 23 package software. In the data analysis, descriptive statistics, Mann-Whitney U and Kruskal Wallis H Tests were used. It was discovered that economic sustainability practices have statistical differences between gender and industry. In regards to social and environmental sustainability, there were no statistical differences according to demographic profile, except for age group and industry. This study helps to increase understanding of manufacturing SMEs about business sustainability.